EFFECT OF ORGANIZATIONAL CULTURE, COMPENSATION, AND PERSONALITY TRAITS TOWARDS EMPLOYEE PERFORMANCE IN TANGERANG PRIVATE UNIVERSITY: MEDIATING ROLE OF INNOVATIVE WORK BEHAVIOUR - Ani Ratnasari; Bahtiar Usman; Deasy Aseanty (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Objective – This research aims to analyse effect of organizational culture, compensation and personality traits on employee performance in Tangerang private university using innovative work behaviour as intervening variables. Design/methodology/approach – This research uses quantitative approach with the unit of analysis 306 lecturer working in 11 private universities in Tangerang. Cross-sectional and one-shot data collection was carried out through distribution of google form questionnaires. The proposed model includes 10 hypotheses tested using Structural Equation Modelling (SEM). Findings – Majority of respondents are male, aged < 30 year, master degree, married, average monthly income > IDR 5-10 million, work experience > 1-5 year, and expert assistant. The result shows that compensation, personality traits and innovative work behaviour has positive and significant effect on employee performance, but organizational culture does not have an effect on employee performance. Innovative work behaviour shows a full mediation effect of organizational culture on employee performance.  Theoretical Implications – This research could enrich the body of knowledge about organizational culture, compensation, personality traits, innovative work behaviour and employee performance. Unlike the results of previous studies, this study shows that organizational culture has no effect on employee performance of private university lectures. Managerial Implications – Improvement of employee performance could be improved through 1) University leaders explain in detail about vision and mission of the university, 2) Maintaining fair compensation based on work performance, 3) Lectures keep high motivation to give best effort, 4) Maintaining innovative work behaviour to find new teaching and research methods.  Originality/value – Research about effect of organizational culture, compensation and personality traits on employee performance mediated by innovative work behaviour in private university are still very limited.